ANALISIS FAKTOR-FAKTOR YANG PALING MEMPENGARUHI KEPUASAN KONSUMEN WARNET DI SEKITAR UNIVERSITAS TARUMANAGARA - Cokki Cokki (Business Management Journal, 2017)
The empirical research investigated factors that affect consumer satifaction prior to purchasing a product. This research focused on the purchase of internet renting services. The purpose of this research was to understand consumer behaviour in purchasing internet renting services. The results were used to make an effective and efficient marketing strategy as well to investigate further about consumer behaviour in internet renting services. The investigation used consumer analysis and operational analysis. Correlation design with purchasing decision as dependent variable, together with location, price, facility, internet access speed, comfort, services as independent variables were investigated and analyzed using SPSS 13.0. This research results indicated that the purchasing decision is affected mostly by internet access speed and facility factors with location, price, facility, comfort and servicess as less factors. Keywords : Consumer Satifaction, Consumer Behaviour, Internet Rental Service